IMPROVING PATIENT EXPERIENCE: IMPLEMENTATION OF A PRODUCT-SERVICE SYSTEM WITH ALTERNATIVE TREATMENT - Daffa Rozano (Veteran Economics, Management, & Accounting Review, 2024)
This research paper investigates applying a product-service system (PSS) approach in Guru Singa Alternative Treatment to enhance the patient experience and add value to their services. The study comprises three key steps: determining the quadrant position of the products/services, selecting alternative PSS quadrants, and identifying needs and resources. Analysis of a questionnaire and insights from the owner revealed that Guru Singa Alternative Treatment falls under the quadrant of Service Providing.. To address these needs, we propose two solutions. Firstly, a free consultation program is recommended, providing patients expert guidance and support during treatment and recovery. Additionally, educational initiatives will promote bone health and injury prevention. Secondly, an integrated recovery and rehabilitation program is suggested for physical therapy, occupational therapy, and psychological counseling. This research contributes to developing effective fracture recovery practices and improved patient care in alternative treatment facilities. Adopting the PSS approach offers promising opportunities for innovation and advancing healthcare quality in alternative treatments